Export Diversification in Africa : The Importance of Good Trade Logistics - Huria, Ankur; Brenton, Paul (World Bank, Washington, DC, 2015)
Economic activity in many African countries remains highly concentrated and exports are often dominated by mineral resources or a few primary products. The World Bank’s 2011 report on light manufacturing in Africa identified poor trade logistics performance as a constraint that especially penalized African exporters that relied on imported inputs, very often making them uncompetitive. The report highlighted research that demonstrated how poor logistics added roughly a 10 percent production cost penalty in Ethiopia, Tanzania, and Zambia across the five subsectors of light manufacturing where opportunities were identified as greatest in Africa. The report outlined how in Africa poor trade logistics increase production costs (often wiping out the labor cost advantage) and lead to long and unreliable delivery times, making local firm’s unattractive suppliers to lead firms in global value chains (GVCs), particularly for light manufacturing. This note seeks to contribute to a review of progress in achieving export diversification through greater exports of light manufacturing products. It looks at recent trends in the exports of the five categories of light manufacturing identified as having strong potential in Africa. The note reviews progress in improving trade logistics in Sub-Saharan Africa, with a focus on the three countries highlighted in the light manufacturing study: Ethiopia, Tanzania, and Zambia, and additionally Kenya and Uganda.